PENGENDALIAN KUALITAS PRODUK DENGAN PENDEKATAN SIX SIGMA PADA UMKM TAHU XY - Inez Kusuma Wardhani (2021)
UMKM Tahu XY is an industry engaged in the food sector with the final product in the form of tofu. Based on data obtained from companies from June 2021-July 2021 producing tofu as many as 249,903 products and defect products as many as 14,558 products. Therefore, UMKM Tahu XY requires quality control in the production process. This study aims to identify defects in the product, identify the causes of defects in the product and provide a design improvement in the tofu production process. The six sigma and FMEA methods are chosen for quality control of tofu products. The results of the study found the type of defect found in UMKM Tahu XY that is, defect size, defect tecture, aroma defect, acid defect and dirt defect. The highest defect is a texture defect with a total of 8,433. based on the calculation results obtained the sigma value is 3.77412928 so the company is at level 3σ. Then an analysis is carried out using a fishbone diagram to find out the cause of the defect. Based on the fishbone diagram there are 3 factors that cause the defect product namely man, machine and method. UMKM Tahu XY can reduce the defect produced by the repair design that has been provided by the author, which makes SOPs about time in the production process, replaces tofu cutters, trains workers and conducts surveillance. Then a simulation is made based on the improvements given and obtained results with an increase in output of 27 tofu molds or 9.8%.